2009
DOI: 10.1177/039463200902200227
|View full text |Cite
|
Sign up to set email alerts
|

Apicidin, the Histone Deacetylase Inhibitor, Suppresses TH1 Polarization of Murine Bone Marrow-Derived Dendritic Cells

Abstract: Apicidin is a fungal metabolite shown to exhibit anti-proliferative, anti-invasive, and anti-inflammatory properties by the inhibition of histone deacetylase (HDAC). However, the effects of apicidin on the maturation and immunostimulatory function of dendritic cells (DCs) remain unknown. In this study, we investigated whether apicidin modulates surface molecule expression, cytokine production, endocytosis capacity, and underlying signaling pathways in murine bone marrow-derived DCs. We observed that apicidin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
(36 reference statements)
2
14
0
Order By: Relevance
“…Thus, we consider that HDAi alter dendritic cells to a tolerogenic-like phenotype. Some previous reports have reported that histone deacetylase (HDAC) inhibition alters dendritic cell function when lipopolysaccharide was used to stimulate and differentiate dendritic cells [34]. We have found similar results using ZyA, which signals through Dectin-1 and TLR-2, instead of lipopolysaccharide, which utilizes TLR-4, illustrating that HDAC inhibition alters dendritic cell function regardless of the stimulation.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, we consider that HDAi alter dendritic cells to a tolerogenic-like phenotype. Some previous reports have reported that histone deacetylase (HDAC) inhibition alters dendritic cell function when lipopolysaccharide was used to stimulate and differentiate dendritic cells [34]. We have found similar results using ZyA, which signals through Dectin-1 and TLR-2, instead of lipopolysaccharide, which utilizes TLR-4, illustrating that HDAC inhibition alters dendritic cell function regardless of the stimulation.…”
Section: Discussionsupporting
confidence: 82%
“…The authors report that LAQ824 also inhibits DC and macrophage chemotaxis without altering that of neutrophils. As a whole, this study is in keeping with that of Jung et al showing that the HDACi apicidin suppresses DC-dependent Th1 polarization (34). Several reports, therefore, confirm that HDACi impairs DC functions and the ensuing T-cell proliferation remarkably through mechanisms related to modulation of specific gene expression, and not because of an overall deregulation of gene transcription.…”
Section: Possible Mechanisms Underlying the Therapeutic Effects Of Hdsupporting
confidence: 91%
“…Reviewed in (74) Reduced disease severity in dextran sodium sulfate and trinitrobenzene sulfonic acid (TNBS) colitis (143,144) Decreased cytokine levels in colitis model (143,144) Reduced severity of colitis in HDAC-9-deficient mice (145) Suppression of COX-2 activation in colon cells (146) Immunosuppressive properties Reviewed in (43,75,76) Survival benefit in GvHD (71,72,147) Sparing effect on graft versus leukemia (71) Increased Foxp3 + T-regulatory cells (148,149) Reduced incidence of diabetes in NOD mouse (36) Induction of antigen-specific anergy in lymphocytes (150) Improved allograft transplantation (148,151) Induction of IDO and inhibition of dendritic cell maturation (44) Reduced nephritis in lupus-prone mice (119,120) Decrease disease severity in experimental allergic encephalitis (76,152) Suppression of Th1 polarization of murine dendritic cells (153) Inhibition of IL-2 gene expression in T cells (154,155) Reduced cytokine production in primary human T cells stimulated with anti-CD3/CD28 (156) Inhibition of CD154 (CD40L) expression in T cells (157) Models of arthritis Reviewed in (25,26) Reduced joint destruction in collagen-induced arthritis (25,158,159) Decreased bone and cartilage loss (25) Lower cytokine and chemokine levels (23,24) Decreased synovial cell proliferation (160) Abrogation of TGFβ-1-induced fibroblast-myofibroblast differentiation (161) Inhibition of IL-1β-induced matrix metalloproteinase expression in human articular chondrocytes (162)…”
Section: Models Of Inflammatory Bowel Diseasementioning
confidence: 99%